The differential impact of natural killer (NK) cell education via KIR2DL3 and KIR3DL1 on CCL4 secretion in the context of in‐vitro HIV infection. (9th September 2016) - Lisovsky, I.; Isitman, G.; Tremblay‐McLean, A.; Song, R.; DaFonseca, S.; Lebouchẻ, B.; Routy, J.‐P.; Bruneau, J.; Bernard, N. F.
Summary: Carriage of certain inhibitory natural killer (NK) cell receptor (iNKR)/HLA ligand pairs is associated with protection from infection and slow time to AIDS implicating NK cells in HIV control. NK cells acquire functional potential through education, which requires the engagement of iNKRs by their human leucocyte antigen (HLA) ligands. HIV infection down‐regulates cell surface HLA‐A/B, but not HLA‐C/E. We investigated how NK cell populations expressing combinations of the iNKRs NKG2A, KIR2DL3 (2DL3) and KIR3DL1 (3DL1) responded to autologous HIV infected CD4 (iCD4) cells. Purified NK cells from HIV‐uninfected individuals were stimulated with autologous HIV iCD4 or uninfected CD4 T cells. Using flow cytometry we gated on each of the 8 NKG2A +/– 2DL3 +/– 3DL1 +/‐ populations and analysed all possible combinations of interferon (IFN)‐γ, CCL4 and CD107a functional subsets responding to iCD4 cells. Infected CD4 cells induced differential frequencies of NKG2A +/– 2DL3 +/– 3DL1 +/– populations with total IFN‐γ +, CCL4 + and CD107a + functional profiles. 2DL3 + NKG2A + NK cells had a higher frequency of responses to iCD4 than other populations studied. A higher frequency of 2DL3 + NK cells responded to iCD4 from individuals that were not HLA‐C1 homozygotes. These results show that 2DL3 + NK cells are mediators of HIV‐specific responses. Furthermore, responses of NK cell populations to iCD4 are influenced not only by NK cell education through specific KIR/HLA pairs, but also by differential HIV‐mediated changes in HLA expression. Abstract : Inhibitory NK cell receptor/HLA ligand pairs are important determinants of NK cell function through a process known as NK cell education. Certain of these are associated with protection from infection and slow time to AIDS implicating NK cells in HIV control. Our results show that NKG2A+KIR2DL3+ NK cells are mediators of HIV‐specific responses, and these responses are influenced, not only, by NK cell education through specific KIR/HLA pairs, but also by differential HIV mediated changes in HLA expression.